Determination of dissolved natural thorium and uranium in Horonobe and Mizunami Underground Research Laboratory groundwater and its thermodynamic analysis. Issue 3 (4th March 2017) - Sasaki, Takayuki; Koukami, Takayuki; Kobayashi, Taishi; Kirishima, Akira; Murakami, Hiroaki; Amano, Yuki; Mizuno, Takashi; Iwatsuki, Teruki; Sasamoto, Hiroshi; Miyakawa, Kazuya
ABSTRACT: At two underground research laboratories situated at Horonobe and Mizunami, Japan, trace amounts of natural thorium and uranium dissolved in deep groundwater were investigated with the help of chemical pre-concentration method. The groundwater was sampled from underground boreholes under the geochemical condition of no atmospheric exposure, and the colloid contribution was checked by in situ two size-fractionated ultrafiltration systems. A rough decrease by half in the concentration after in situ filtration suggested the presence of natural colloids and suspended matter that were carriers of a portion of the elements. The Th and U concentrations in groundwater after 10 kDa filtration was evaluated as dissolved species, and was identified thermodynamically using existing hydrogeological and geochemical data, such as the mineral components in the groundwater at a given pH, ionic strength, concentration of co-existing ions, redox potential, and a hypothetical solubility-limiting solid phase. The crystalline solid phase of tetravalent thorium and uranium dioxides made the solubility very low compared with that of the amorphous phase.